Role of Working Memory Storage and Attention Focus Switching in Children's Comprehension of Spoken Object Relative Sentences. (20th May 2014) - Finney, Mianisha C.; Montgomery, James W.; Gillam, Ronald B.; Evans, Julia L.
Abstract : The present study evaluated a two-mechanism memory model of the online auditory comprehension of object relative (OR) sentences in 7–11-year-old typically developing children. Mechanisms of interest included working memory storage (WMS) and attention focus switching. We predicted that both mechanisms would be important for comprehension. Forty-four children completed a listening span task indexing WMS, an auditory attention focus switching task, and an agent selection task indexing spoken sentence comprehension. Regression analyses indicated that WMS and attention focus switching accuracy each accounted for significant and unique variance in the children's OR comprehension after accounting for age. Results were interpreted to suggest that WMS is important for OR comprehension by supporting children's ability to retain both noun phrase 1 and noun phrase 2 prior to their reactivating noun phrase 1 from memory in order to integrate it into a developing structure. Attention focus switching was interpreted to be critical in supporting children's noun phrase 1 reactivation, as they needed to switch their focus of attention momentarily away from ongoing language processing to memory retrieval.